The Level of Job Satisfaction of Young Farmers Subsidized by European Rural Measures: Evidence from Northern Greece - Papadopoulou, Dimitra G; Papadaki-Klavdianou , Afroditi; Michailidis , Anastasios; Partalidou, Maria (Asian Journal of Agriculture and Rural Development, 2019)
This paper examines the job satisfaction of a sample of 182 young farmers from northern Greece who are beneficiaries of support policies, as well as the factors influencing it. The results indicate that young farmers are little satisfied in their job and the practices applied by institutional bodies are the main cause of their job dissatisfaction. Nevertheless, they like the content and nature of their job. Residing in peri-urban rural areas, the intention to continue exercising the farming profession, the sense of achievement, training opportunities, and optimism have positive effects on job satisfaction. However, considering that young people in mountainous areas have a strong sense of job dissatisfaction and claim that they are less likely to continue farming there is a need for integrated development of the countryside focused on the local needs of each area.